1994
DOI: 10.1128/jcm.32.10.2350-2352.1994
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of genital Chlamydia trachomatis infections in asymptomatic males by testing urine by PCR

Abstract: An enzyme-linked immunosorbent assay (EIA) (MikroTrak; Syva) was compared with PCR (Amplicor; Roche) for detection of Chlamydia trachomatis in first-void urine (FVU) from 184 men attending a skin and venereal disease clinic. The prevalence of C. trachomatis in the population studied was 18.5%. Discrepant results between Syva EIA and Roche PCR were retested by using major outer membrane protein primer-based PCR. After retesting, the sensitivity, the specificity, and the positive and negative predictive values f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…Our results show that PCR testing of FVU specimens appears to overcome these concerns raised about screening asymptomatic men by EIA testing of FVU specimens. Other studies with populations with higher prevalences of chlamydial infections have also reported similar findings (9,12,25). Initial experience with another DNA amplification technique, the ligase chain reaction, also indicates that it is highly sensitive when it is used on FVU specimens from men, even if they are asymptomatic (8).…”
Section: Discussionmentioning
confidence: 56%
“…Our results show that PCR testing of FVU specimens appears to overcome these concerns raised about screening asymptomatic men by EIA testing of FVU specimens. Other studies with populations with higher prevalences of chlamydial infections have also reported similar findings (9,12,25). Initial experience with another DNA amplification technique, the ligase chain reaction, also indicates that it is highly sensitive when it is used on FVU specimens from men, even if they are asymptomatic (8).…”
Section: Discussionmentioning
confidence: 56%
“…The package insert did not recommend retesting specimens in a gray zone. Amplicor Chlamydia (Roche Molecular Systems, Branchburg, N.J.) PCR was performed according to the manufacturer's instructions and has been described in previous reports (6,9,17). Specimens with absorbances of 0.5 or above were considered positive, and those with absorbances below 0.2 were considered negative.…”
mentioning
confidence: 99%
“…Many asymptomatic individuals are also reluctant to undergo urethral sampling. Culture has a low sensitivity with voided urine (8)(9)(10)17). Gene-based nonamplification techniques have proved to be as sensitive as EIAs when they are used to detect C. trachomatis in urine.…”
mentioning
confidence: 99%